Incidência e fatores associados à sífilis congênita em Belo Horizonte (MG): estudo prospectivo não concorrente, 2011-2013 - Solange Maria Nonato (2015)
Congenital syphilis is a severe disease, preventable and can be eliminated with timely diagnosis and treatment of pregnant women with syphilis. The qualite of antenal care quality makes a significant difference to reducing adverse outcomes due to syphilis in pregnant women. In Belo Horizonte, despite the expansion of the Family Health Program and improving access to prenatal care, the incidence of congenital syphilis has increased in recent years at a worrying rate. Thus, the aim of this study was to estimate the incidence and factors associated with the occurrence of congenital syphilis in newborns of pregnant women who performed prenatal care in the basic health units in Belo Horizonte, from November 2010 to September 2013. To this end, we performed a historical cohort study involving 353 pregnant women with syphilis, selected from Sisrede among 22 720 pregnant women who performed non treponemal test (VDRL), from July 2011 to December 2012. The information about socioeconomic characteristics, obstetric history and current pregnancy were collected from the electronic medical record. The estimated prevalence of syphilis among pregnant women was 1.6% and the incidence of congenital syphilis was 33.4%. There was a predominance of pregnant women aged greater than or equal to 20 years (81.6%), with low education (74.1%), non-white (61.8%), living alone or with family members (65, 5%) and had six or more consultations (65.2%) of prenatal care; 51.5% and 56.6% respectively, stardet the prenatal and performed the first VDRL after the first trimester of pregnancy. Factors associated with the occurrence of congenital syphilis were younger maternal age 20 years (RR = 1.44, 95% CI 1.05 to 1.99), less education than eight years of study (RR = 1.64; IC 95% 1.02 to 2.62), late onset of prenatal care (RR = 1.65, 95% CI 1.21 to 2.27), less than six prenatal consultations (RR = 1.37 , 95% CI 1.02 to 1.84), have not done the VDRL in the first trimester (RR = 1.68, 95% CI 1.21 to 2.32), title of the first VDRL greater than or equal to 1: 8 (RR = 2.86, 95% CI 1.85 to 4.41) and title of the latest VDRL performed prenatal greater than or equal to 1: 8 (RR = 2.36, 95% CI 1.62 3.42), and negative association with a history of pregnancy (RR = 0.69, 95% CI 0.49 to 0.98) and abortion (RR = 0.64, 95% CI 0.42 to 0, 99). The results show failures in prenatal care and indicate the need for new strategies to reduce vertical transmission of syphilis. The monitoring of pregnant women VDRL results is a strategy to diagnose and timely treat pregnant women with syphilis.